2010
DOI: 10.1161/strokeaha.109.563726
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Progenitor Cells in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy

Abstract: Background and Purpose— Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited disease due to cerebral microangiopathy presenting with variable pictures, including stroke, progressive cognitive impairment, and disability. Mechanisms leading from vessel structural changes to parenchymal damage and eventually to clinical expression are not fully understood. Among pathogenic processes, endothelial dysfunction has been hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…Moreover, in CADASIL, CPC levels were associated with clinical/functional indicators of disease severity, suggesting that these cells might have a role in the determination of the final phenotypic expression of the disease. 90 Data heterogeneity may be explained by a number of differences in studies design. A first major concern relates to the different cohorts under investigation: some studies were conducted in the framework of population-based surveys of elderly individuals, while others investigated hospital cohorts without age limits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in CADASIL, CPC levels were associated with clinical/functional indicators of disease severity, suggesting that these cells might have a role in the determination of the final phenotypic expression of the disease. 90 Data heterogeneity may be explained by a number of differences in studies design. A first major concern relates to the different cohorts under investigation: some studies were conducted in the framework of population-based surveys of elderly individuals, while others investigated hospital cohorts without age limits.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the "yellow capillaries" may be the results of endothelial damage by CADASIL-associated cerebral capillary degeneration, and the damaged endothelium is replaced by the bone marrow-derived endothelial cells. In support of this notion, a clinical study showed that the levels of endothelial progenitor cells (EPCs) in the blood of CADASIL patients were significantly lower than in control subjects, and that CADASIL patients with infarcts and dementia displayed a reduction in circulating progenitor cells (Pescini et al, 2010). The reduction of circulating EPCs in CADASIL may be due to the persistent consumption of EPCs to replace the damaged endothelium during the progressive degeneration of cerebral vessels.…”
Section: Prevention Of Cadasil-associated Vsmc Degeneration and Cerebmentioning
confidence: 97%
“…In cerebrovascular medicine, other recent studies demonstrated low levels of circulating EPCs in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy [30], a correlation between low EPC levels and severe age-related white matter changes [31] and higher levels in patients with moyamoya disease [32]. …”
Section: Epc As a Risk Marker In Vascular Diseasesmentioning
confidence: 99%